Comparison kinematic patterns between the Star Excursion Balance test and Y-Balance test in elite athletes - Ko, J. (Korean Journal of Sport Biomechanics, 2017)
Objective: The Star Excursion Balance Test (SEBT) and Y-Balance Test (YBT) have been commonly applied to measure dynamic postural stability ability. These two tests are utilized interchangeably in various settings. However, they could in fact require different movements to assess dynamic postural stability, as one uses a platform and different measuring techniques than the other. The purpose of this study was to determine if there was a significant difference in the kinematic patterns in physically active population while performing the SEBT and the YBT. Method: Seventy participants performed in the Anterior (AN), Posteromedial (PM), and Posterolateral (PL) directions of the SEBT and the YBT. The kinematics of hip, knee, and ankle in sagittal plane was calculated and analyzed. Paired-sample t-tests were performed to compare joint angular displacement in the ankle, knee, and hip between the SEBT and the YBT. Results: Significant differences in angular displacement at the hip, knee, and ankle joints in the sagittal plane between performance on the SEBT and on the YBT were observed. Conclusion: Clinicians and researchers should not apply these dynamic postural control tasks interchangeably from one task to another. There appear to be kinematic pattern differences between tests in healthy physical active population.